COOPERATIVE ACCOUNTING TRAINING FOR ONE-HEARTED PARENT WASTE BANK COOPERATIVES - Etty Murwaningsari; Deni Darmawati; Sofie Sofie; Yvonne Augustine; Diana Frederica (Sean Institute, 2023)
The implementation of PKM activities with the theme